Interdiction des emblèmes berbères et occupation des espaces symboliques : amazighité versus algérianité ? - Mohand Tilmatine (L’Année du Maghreb)
The irruption of the Amazigh emblem alongside the Algerian national flag, proudly displayed during the massive demonstrations that punctuate since February 16, 2019 the Algerian Fridays is a phenomenon undoubtedly new and remarkable. Indeed, it reflects the conquest of a new symbolic space so far relatively confined in Kabylia and to a lesser extent in other Berber-speaking regions such as Aurès or Mzab. The announced ban on this emblem, promptly followed by the imprisonment of some 30 protesters, opened a gap in the apparent homogeneity that seemed to unify the new “smile revolution”, but also (re)opened a debate on symbols and identity references of a future Algerian republic. The text will tackle this issue by focusing on the symbolic stakes and the underlying identity and politics that support this “war of flags” and the persecution of “other emblems” than the Algerian national flag taken by Ahmed Gaid Salah, the new strong man of the Algerian regime since the fall of President Bouteflika.